The Problem of the Potsherd: Job 2:8 in a New Perspective - Wolde, Ellen J. van (Old Testament essays, 2018)
The famous verse in the prologue of the book of Job, which is commonly translated with "Job took a potsherd to scrape himself while he was sitting among the ashes, " is the object of study here. In this analysis of Job 2:8, three components are extensively discussed; (1) The syntactic structure that shows that the subject of the action of "taking" is the satan and not Job; (2) The semantic analysis of the occurrences of the noun .--, which demonstrates that this word does not designate "potsherd," but "pot"; and (3) The semantic analysis of the infinitive hitpael .-.-., which explains the satan's goal in bringing Job a pot, namely to squeeze out his inflamed boils that cover him from head to toe.